Upaya Peningkatan Prestasi Akademis Dan Non Akademis Melalui Open House, Pameran Dan Pentas Pendidikan Di Smpn 4 Malang - Sukirman, Sukirman (J-PAI: Jurnal Pendidikan Agama Islam, 2015)
This study focused on single object is Junior High School 4 Malang. This study uses qualitative approach by using observation technique, interview, and documentation. In this research, for data processing, researcher use descriptive qualitative method (non statatistic) such as collecting data,reduction data, and present the data or report the data, then analyze and conclude. The activity of Open House, exhibition, and education expo in Junior High School 4 Malang has been done well. Those promotions has strategic bound in order to develop the school which has high quality. The location of this school is on Jl. Veteran is one of favorite school inMalang that every year the average mark of PSB Online and National Examination always increase, besides non academic achievement (art and scout).Keywords: Open House, Exhibition, Education Expo, Achievement,Academic, non Academic